Alaterações das características químicas e físico-químicas do suco de goiaba (Psidium guajava L.) durante o processamento - Fernandes, Aline Gurgel (2007)
Fruit juices are important vitamin sources, mineral salts, organic acids and fibers, and including in the diet of the population, they can help to keep people healthy. During the stages of juice processing, some modifications in the fruit compounds can happen, affecting its sensorial and nutritional properties. Researches on the effects of processing on the nutritional compound tropical juice are scarce. Usually, only vitamin C losses are evaluated. This study determined the possible chemical and physical-chemical changes during the stages of guava tropical juice processing (extration, formulation / homogenization and pausterization) and storage (30 days). Soluble solids, pH, acidity, reducing sugars, total sugars, water activity, colour, vitamin C, anthocyanins, carotenoids, phenolic compounds and pectinametilesterase activity were analysed. We saw that only pH, carotenoids and pectinametilesterase activity parameters showed significant variations during the stages of juice processing. At the end of the processing, vitamin C, phenolic compounds and total anthocyanins contents were high, and it was an increase of total carotenoid amount in the guava juice. For the guava juice stored during 30 days it was observed no significant difference between the times zero and thirty days, for the analysed parameters. We conclude that since the chemical and physicochemical characteristics were affected just a little by processing and stored during 30 days, the hot fill processing, the glass packings used and added conservant were good factors of product preservation in this study.